2008
DOI: 10.1063/1.3013896
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of underwater granular avalanches: Influence of the initial volume fraction

Abstract: We experimentally investigate how a layer of granular material fully immersed in a liquid starts to flow when suddenly inclined from a horizontal position. The flow is shown to strongly depend on the initial volume fraction, its initiation being dramatically delayed by a slight initial compaction. A model, which takes into account the dilatant behavior of the granular material and the coupling with the interstitial fluid, captures the main experimental features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
118
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 20 publications
10
118
1
Order By: Relevance
“…The presence of a fluid (rather than air) not only modifies the interstitial pore pressures, but also couples the stress carried by the particles to that carried by the fluid flowing through gaps in the grain matrix (Iverson & LaHusen 1989;Iverson 1997Iverson , 2005. This coupling is particularly significant in unsteady flows, since local changes in the particle volume fraction allow large excess pore pressures to develop, which in turn feedback on the granular motion (du Pont et al 2003;Muite, Hunt & Joseph 2004;Pailha, Nicolas & Pouliquen 2008;Pailha & Pouliquen 2009). However, for steady, dense granular flows such as those sketched in figure 2, the large number of particle-particle contacts mean that frictional interactions are still dominant in …”
Section: Recirculating Particle Motionmentioning
confidence: 99%
“…The presence of a fluid (rather than air) not only modifies the interstitial pore pressures, but also couples the stress carried by the particles to that carried by the fluid flowing through gaps in the grain matrix (Iverson & LaHusen 1989;Iverson 1997Iverson , 2005. This coupling is particularly significant in unsteady flows, since local changes in the particle volume fraction allow large excess pore pressures to develop, which in turn feedback on the granular motion (du Pont et al 2003;Muite, Hunt & Joseph 2004;Pailha, Nicolas & Pouliquen 2008;Pailha & Pouliquen 2009). However, for steady, dense granular flows such as those sketched in figure 2, the large number of particle-particle contacts mean that frictional interactions are still dominant in …”
Section: Recirculating Particle Motionmentioning
confidence: 99%
“…Note that even if the solid volume fraction is used as a control parameter it reflects only partially the complexity of the granular microstructure from which originate the local mechanisms responsible for the micro-failures described in [5][6][7][8][9]. Other quantities should be more relevant than the solid volume fraction as for instance the dilatancy angle [12,23] or the mean coordination number. Moreover, to analyze the role of boundary conditions, we will vary the geometry of the cell by changing independently of each other the width, height and depth of the sample.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…By now, only very few studies have investigated the transient regime [10][11][12] while many works have dealt with the steady regime of dry surface avalanche flows leading in particular to the proposal of a local granular rheology for dense flows (see [13] and references therein). According to the definition of three regimes of avalanches in fluids [14], the local rheology has been subsequently extended to the case of submarine granular flows down inclined planes [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the fluid has a twofold effect on the granular motion. On one hand, it may reduce the granular kinetic energy by developing negative pore pressure and fluid viscous drag force (Iverson et al 2000;Pailha et al 1994;Topin et al 2011). On the other hand, it can also enhance the granular flow by lubricating the granular mixture.…”
Section: Introductionmentioning
confidence: 99%